2021
DOI: 10.1111/mmi.14839
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of classical complement activation and IgM to the control of Rickettsia infection

Abstract: Pathogenic Rickettsia are obligate intracellular bacteria and the etiologic agents of many life‐threatening infectious diseases. Due to the serious nature of these infections, it is imperative to both identify the responsive immune sensory pathways and understand the associated immune mechanisms that restrict Rickettsia proliferation. Previous studies have demonstrated that the mammalian complement system is both activated during Rickettsia infection and contributes to the immune response to infection. To furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…The methods by which the activity of the complement system is measured are similar to those used in the determination of cytokines. Enumerated methods include ELISA and ELISPOT immunological methods, real-time PCR, or the determination of activity and concentration of individual complement components [ 150 ].…”
Section: Diagnostics Of the Inflammatory Process In Admentioning
confidence: 99%
“…The methods by which the activity of the complement system is measured are similar to those used in the determination of cytokines. Enumerated methods include ELISA and ELISPOT immunological methods, real-time PCR, or the determination of activity and concentration of individual complement components [ 150 ].…”
Section: Diagnostics Of the Inflammatory Process In Admentioning
confidence: 99%
“…In this case, the pathomechanisms may relate to a delayed IgG class switch, altered T-cell response, and altered cytokine levels ( 114 ). Similarly, the pathogen burden in various organs during infections with Rickettsia , yet another intracellular pathogen transmitted among others by ticks, was significantly increased in C1qKO mice ( 115 ).…”
Section: Resultsmentioning
confidence: 99%
“…The anaphylatoxin receptors therefore join an ever-increasing repertoire of innate immune receptors that can indirectly or directly sense the presence of Rickettsia bacilli. Previous findings have demonstrated that the innate immune system can directly detect Rickettsia through preexisting IgM molecules that activate the complement system to produce anaphylatoxins ( 91 ). Therefore, the pathway from (i) IgM recognition of the bacterial surface, (ii) anaphylatoxin production, and (iii) anaphylatoxin receptor agonism is a strong surveillance pathway for alerting mammalian cells about the presence of Rickettsia .…”
Section: Discussionmentioning
confidence: 99%
“…C3a and C5a concentrations were determined by an enzyme-linked immunosorbent assay as previously described ( 91 ). Appropriate media were harvested on day 3 and used for the evaluation of complement activation.…”
Section: Methodsmentioning
confidence: 99%